Enhancement of non-motorized three degree of freedom assessment tool for stroke patients - Mazlan, Sulaiman (2018)
The use of robotic devices for physical rehabilitation of the upper limb following brain injury can assist physiotherapists in rehabilitation program. The presence of robotic rehabilitator will help physiotherapists to assess the stroke patients effectively during their rehabilitation process. Although researchers in the field of robotic rehabilitation has designed the robotic assessment tools, it’s still need improvement in term of design complexity. The goal of this project is to develop non-motorized device namely iRest 2.0 to enhance the previous iRest design that consist of reaching, forearm rotation and grasping movements. Moreover, The iRest 2.0 is developed more compact and portable compare to the iRest in term of weight and dimension. Besides, a study with 5 healthy subject who that has no injury history of upper limb was carried out to analyse the performance of iRest 2.0. This performance analysis was based on the three assessment module (Draw Capital I, Draw Diamond, and Draw Circle). Results shows the positive outcome where almost all the kinematic variables for the three assessment module had positively improved when using iRest 2.0 compared to iRest. The results of this project suggest that a nonmotorized system such as iRest 2.0 could be used to replace iRest in order to assess the hand function of stroke patients.